Time evolution of photoconductivity in TiO2 electrodes fabricated by a sol gel method - Xie, Z; Burlakov, V; Henry, B; Kirov, K; Grovenor, C; Assender, H; Briggs, G; Kano, M; Tsukahara, Y (2005)
We report here on the time evolution of photoconductivity under continuous illumination in nanocrystalline TiO2 samples prepared by a sol gel method, and also on the conductivity decay once the illumination is switched off. We observe strong dependence of the photoconductivity on the illumination intensity for both processes. It is found that the conductivity decay after high-intensity illumination is slower than after low-intensity illumination, and we have attempted to explain these experimental results using a model involving hole trapping-detrapping processes.